Does Ecophysiology Determine Invasion Success? A Comparison between the Invasive Boatman Trichocorixa verticalis verticalis and the Native Sigara lateralis (Hemiptera, Corixidae) in South-West Spain - Coccia, Cristina; Calosi, Piero; Boyero, Luz; Green, Andy J.; Bilton, David T. (PLOS ONE, 2013)
Background Trichocorixa verticalis verticalis, a native of North America, is the only alien corixid identified in Europe. First detected in 1997 in southern Portugal, it has spread into south-west Spain including Doñana National Park. Its impact on native taxa in the same area is unclear, but it is the dominant species in several permanent, saline wetlands. Methodology/Principal Findings We investigated whether the ecophysiology of this alien species favours its spread in the Iberian Peninsula and its relative success in saline areas. We compared physiological responses to heating (Critical Thermal maximum), cooling (Critical Thermal minimum) and freezing (Super Cooling Point) in the native Sigara lateralis and introduced T. v. verticalis acclimated to different temperatures and salinities. The larger S. lateralis generally outperformed T. v. verticalis and appeared to possess a broader thermal tolerance range. In both taxa, CTmax was highest in animals exposed to a combination of high conductivities and relatively low acclimation temperatures. However, CTmax was generally higher in T. v. verticalis and lower in S. lateralis when acclimated at higher temperatures. CTmin were lower (greater tolerance to cold) after acclimation to high conductivities in T. v. verticalis, and following acclimation to low conductivities in S. lateralis. Both acclimation temperature and conductivity influenced corixids' freezing tolerance; however, only in T. v. verticalis did SCP decrease after exposure to both high temperature and conductivity. T. v. verticalis showed a higher range of mean responses over all treatments. Conclusions Whilst the native S. lateralis may have a broader thermal range, the alien species performs particularly well at higher salinities and temperatures and this ability may facilitate its invasion in Mediterranean areas. The greater plasticity of T. v. verticalis may further facilitate its spread in the future, as it may be more able to respond to climate shifts than the native species.